Mathematical Self-Confidence of High School Students: A Study in Costa Rica - Meza-Cascante, Luis Gerardo (2019)
The “mathematical self-confidence” of the Costa Rican secondary education students is studied using the self-confidence subscale of Fennema and Sherman (1976), and the existence of differences in this variable by sex, educational level  and the school geographical location is analyzed as well. The participants in the study were 2984 students (51% female) from the seventh to the eleventh year of official public day schools of the Ministry of Public Education of Costa Rica. The participating schools were selected by simple stratified random sampling and by conglomerates, according to the location area (69.5% urban), and according to the population by province (19.5% Alajuela, 12.5% Cartago, 9.3% Guanacaste, 10.6% Heredia, 10.3% Limon, 9.4% Puntarenas, 28.4% San Jose). The students selected for the study in each school sampled were those belonging to the second group of each educational level (18.9% seventh, 20.5% eighth, 21.4% ninth, 19% tenth, 20.2% eleventh). The results suggest that, jointly, about 78.9% of the students show between high and moderate levels of self confidence. They also indicate the existence of differences in the level of mathematical self confidence according to gender, with lower levels for women, with a medium magnitude of differences. The findings also suggest that there are no differences in the level of mathematical self-confidence among the tenth and eleventh level students, but there are in the ninth level; the latter having the highest index of mathematical self-confidence of the three. The study did not detect differences in the level of mathematical self-confidence among students according to the location of the school. The results suggest, at least, the following lines of research: to delve into the causes of the differences detected in the level of mathematical self-confidence by gender and those that may explain why the level of mathematical self-confidence decreases in the students of Diversified Education.